The Principal's Strategy in Facing The National Assessment in Junior High School - Harahap, Nahwan Sulthoni; Siswanto, Romi; Mujiono (Program S3 Pendidikan Islam Institut Pesantren KH. Abdul Chalim Pacet Mojokerto, 2023)
This study aims to determine the Principal's Strategy in dealing with the National Assessment at Amantul Ummah Junior High School Surabaya, namely: the Principal's Strategy in planning the National Assessment, the Principal's Strategy in implementing the National Assessment, and the Principal's Strategy in evaluating the National Assessment. This research uses a qualitative type and uses a case study approach. Data collection techniques were carried out by means of observation, interviews, and documentation. The presence of researchers in the field is absolutely necessary because the researcher is the main instrument and at the same time acts as the sole data collector. The data sources in this study came from the leaders of Islamic boarding schools, who are in charge of facilities and infrastructure, teaching staff, and advisors to Islamic boarding schools. The data analysis techniques used by researchers were based on Miles and Huberman's theory, namely: data collection, data reduction, data presentation (data display), and verification and conclusion. The validity of the data using the triangulation method. The results of this study indicate that: First, the planning is carried out by the principal by preparing all the needs of the students in facing the National Assessment. Second, the implementation of the National Assessment contains 3 instruments, namely the Minimum Competency Assessment (AKM) including literacy and numeracy tests, Character Surveys, and Learning Environment Surveys. Third, the evaluation is carried out by the principal by looking at the obstacles that occur in the implementation of the National Assessment, namely providing additional hours and deepening the material.